RBI database on Indian economy - Subba Rao, K.G.K. (2005)
The new website launched by the Reserve Bank of India on macroeconomic indicators of the Indian economy, is aimed at providing useful and relevant information to researchers, analysts and general users. It includes significant data on the financial and real sectors, markets, and public and corporate finance. there are certain gaps that can be observed, but once filled, the websit promises to be one of its kind. - Reproduced.
Keywords: Reserve Bank of India; Economic and social development - India; Economic and social development